Pengembangan Media Exploading Box Pop Up 3D Pada Pembelajaran Tematik Kelas IV Sekolah Dasar - Aren Frima; Aswarliansyah Aswarliansyah; Rafelda Octa Wahyuni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to develop a learning product in the form of developing learning media Exploading Box Pop Up 3d in Class IV thematic learning at SD Negeri 76 Lubuklinggau which is valid and practical. This type of research is research and development (R&D) with the development model used, namely 4D (define, design, develop and desiminate). The research sample or the subject of class IV students totaling 16 students. Data collection techniques were carried out through interviews, documentation, and questionnaires. The data analysis technique uses the average score. The results showed that: 1) The quality of the 3d pop up box exploding media seen from the aspect of validity was included in the valid category with an average score of 0.76%; 2) The quality of the 3d pop-up box exploding media is seen from the practicality aspect of student responses with a score of 71.5% and teachers with an average of 91%. So it can be concluded that the pop up 3d pop-up box media in thematic learning of theme 1 sub-theme 1 meets the valid and practical criteria so that it can be used in learning.